SDL 2007: Design for Dependable Systems 13th International SDL Forum Paris, France, September 18-21, 2007 Proceedings - Gaudin, Emmanuel; Najm, Elie.; Reed, Rick.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
th Thisvolumecontainsthepaperspresentedatthe13 SDL Forum,Paris,France entitled (3z(BDesign for Dependable Systems(3y (Band re?ects the intent to have a b- ance between experience reports and research papers related to System Design Languages. The language that was at the heart of the ?rst few SDL Forums was the ITU-T Speci?cation and Description Language de?ned in Z.100, and the app- cation domain was almost entirely ?xed-line telephone communication. Mobile telephony was for the super-rich and electronics in cars was just for radios. Ever since its inception, 30 years ago, the Z.100 language has been used for model-driven development in the telecommunication industry. Nowadays, model-driven engineering is a must for all industries and has been generalized byOMG to allapplicationdomainsascoveredbya paper onanautomotivecase study in this volume. What has been happening over the past few years is that the infrastructure has been put in place providing good support for the mod- driven paradigm, so that the economic bene?t of the approach makes it more of a necessity than a choice for designing dependable systems. The experience report from Motorola in this volume underlines this trend.s
Model Driven Engineering -- A Model-Based Standard for SDL -- Model Driven Development and Code Generation: An Automotive Case Study -- Experiences in Deploying Model-Driven Engineering -- Testing -- TTCN-3 Quality Engineering: Using Learning Techniques to Evaluate Metric Sets -- Using TTCN for Radio Conformance Test Systems -- Testing UML2.0 Models Using TTCN-3 and the UML2.0 Testing Profile -- Language Extensions -- Specifying Input Port Bounds in SDL -- Translatable Finite State Time Machine -- Enhanced Use Case Map Traversal Semantics -- Implementation -- Automated Generation of Micro Protocol Descriptions from SDL Design Specifications -- Synthesizing Components with Sessions from Collaboration-Oriented Service Specifications -- Experiences in Using the SOMT Method to Support the Design and Implementation of a Network Simulator -- Modeling Experience and Extensions -- Consistency of UML/SPT Models -- Formal Verification of Use Case Maps with Real Time Extensions -- Using Probabilist Models for Studying Realistic Systems: A Case Study of Pastry -- OpenComRTOS: An Ultra-Small Network Centric Embedded RTOS Designed Using Formal Modeling -- SDL Design and Performance Evaluation of a Mobility Management Technique for 3GPP LTE Systems.
Keywords: Computer science; Computer organization; Software engineering; Computers; Computer logic; Management information systems; Computer Science; Theory of Computation; Computer Systems Organization and Communication Networks; Software Engineering; Logics and Meanings of Programs; Management of Computing and Information Systems; Electronic books